Nanosecond pulse generation with a gallium nitride saturable absorber - Samsamnun, Farina Saffa Mohamad; Zulkipli, Nur Farhanah; Abdul Khudus, Muhammad Imran Mustafa; Shuhaimi, Ahmad; Abdul Majid, Wan Haliza; Harun, Sulaiman Wadi (OSA - The Optical Society, 2019)
A mode-locked nanosecond Erbium-doped fiber laser (EDFL) was demonstrated using gallium nitrate (GaN) in the form of a polished crystal as a saturable absorber (SA). The GaN film exhibited a modulation depth of 2% with a saturable optical intensity of 0.46 MW/cm2. The laser directly produced nanosecond pulses with stable mode-locking operation at a pump threshold of 149.51 mW. The generated output pulses operated at a 1562 nm central wavelength with a pulse duration and a repetition rate of 485 ns and 967 kHz, respectively. The average output power was 3.068 mW at a pump power of 182.34 mW, corresponding to 3.1 nJ single pulse energy. These results indicate that GaN material has a promising application in ultrafast light generation. © 2018 Optical Society of America under the terms of the OSA Open Access Publishing Agreement.